RESILIENSI PADA NARAPIDANA DITINJAU DARI SPIRITUALITAS DAN DUKUNGAN KELUARGA - Cahyani, Anggun Dwi; Nashori, Fuad (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aimed to inquire about the prisoners' resilience in terms of spirituality and family support. The subjects of this study were 206 male prisoners of the